Spatial and seasonal variability of urinary trihalomethanes concentrations in urban settings - Andrianou, Xanthi; Andra, Syam S.; Makris, Konstantinos C.; Charisiadis, Pantelis (My University, 2014)
A complex network of sources and routes of exposure to disinfection by-products (DBP), such as trihalomethanes (THM) has been driving the wide variability of daily THM intake estimates in environmental epidemiological studies. We hypothesized that the spatiotemporal variability of THM exposures could be differentially expressed with their urinary levels among residents whose households are geographically clustered in district-metered areas (DMA) receiving the same tap water. Each DMA holds unique drinking-water pipe network characteristics, such as pipe length, number of pipe leaking incidences, number of water meters by district, average minimum night flow and average daily demand. The present study assessed the spatial and seasonal variability in urinary THM levels among residents (n=310) of geocoded households belonging to two urban DMA of Nicosia, Cyprus, with contrasting water network properties. First morning urine voids were collected once in summer and then in winter. Results showed that the mean sum of the four urinary THM analytes (TTHM) was significantly higher during summer for residents of both areas. Linear mixed effects models adjusted for age, season and gender, illustrated spatially-resolved differences in creatinine-adjusted urinary chloroform and TTHM levels between the two studied areas, corroborated by differences observed in their pipe network characteristics. Additional research is warranted to shed light on the contribution of spatially-resolved and geographically-clustered environmental exposures coupled with internal biomarker of exposure measurements towards better understanding of health disparities within urban centers.
Keywords: Trihalomethanes; Exposure; Disinfection; Urban; Mixed effects